Determinants of nutritional status among pregnant women in East Shoa zone, Central Ethiopia - Wakwoya, Ermias Bekele; Belachew, Tefera; Girma, Tsinuel (Frontiers in Nutrition, 2022)
Background: Undernutrition is an insufficient intake of energy and nutrients to meet an individual’s needs to maintain good health. Undernutrition during pregnancy severely affects the health of mothers and her baby. Globally it contributes directly or indirectly to 3.5 million maternal deaths annually. This study aimed to determine the level of undernutrition and identify factors associated with undernutrition among pregnant women attending public health facilities in the East Shoa Zone, Central Ethiopia. Methods: Institution-based cross-sectional study was conducted among 472 randomly selected pregnant women from June to August 2021. Sociodemographic, obstetrics, and knowledge related data were collected using a structured interviewer-administered questionnaire, and maternal nutritional status was measured using the Mid Upper Arm Circumference (MUAC). The collected data were entered to EPI‑info version 3.5.4 and then exported to SPSS for windows version 26.0 software for analysis. Multivariable regression analysis was fitted to identify determinants of undernutrition. An adjusted odds ratio with 95% confidence intervals and a p-value less than 0.05 was considered a statistically significant. Results: The prevalence of undernutrition among pregnant women was 13.9% [95% CI: 11.0-17.4]. On multivariable logistic regression model after adjusting background variables, wealth (AOR: 4.9, 95% CI 1.34-18.20), women’s decision making power (AOR: 3.31, 95% CI 1.18-7.79), and nutritional counseling (AOR: 3.53, 95% CI 1.29-9.60) were independently associated with nutritional status of pregnant women. Conclusion: Findings indicated that significant number of pregnant women in the study were undernourished. Higher wealth index, nutritional counseling, and women’s decision-making power were inversely associated with undernutrition. The findings imply the need for economic empowerment of women, enhancing decision-making ability of women and routine and consistent nutritional counseling to decrease undernutrition among pregnant women.